How the media biopoliticized neoliberalism: or, Foucault meets Marx - Miller, Toby (GALÁxIA. Revista Interdisciplinar de Comunicação e Cultura, 2011)
This paper seeks to do two things. First, at a theoretical/exegetical level, it demonstrates important affinities between Foucault and Marx(ism): I contend that an opposition between them is misplaced, and their work can be fruitfully combined. Support for this position can be found in Foucault’s writings on biopower. Second, at an applied level, I draw on biopower to understand the role of the media in the creation of neoliberalism, and their reciprocal relationship.